Ileal digestibility of amino acids for poultry : Doctoral Dissertation - Perttilä, Sini (Natural Resources Institute Finland (Luke), 2020)
The aim of this thesis was to determine the ileal amino acid digestibility values in the most commonly used feed ingredients for poultry in Finland. Four experiments were conducted to determine the apparent amino acid digestibilities of cereals (barley, oats, wheat, triticale and maize) and protein ingredients (rapeseeds, rapeseed cake, rapeseed meal, soybeans, soybean cake, soybean meal and meat and bone meal) for broilers (in publication I, II, III and IV) and adult cockerels (I). The flows of basal endogenous amino acids at the distal ileum of the broilers were determined using a protein-free diet (IV), and standardised ileal amino acid digestibilities were calculated for wheat, soybean meal and rapeseed meal (IV). Further, the effects of β-glucanase supplementation and preservation method of barley on apparent ileal amino acid digestibility (AID) in broilers and cockerels were determined (I). The ileal digestibility values were determined using the slaughter technique and chromium mordanted straw as an indigestible marker. Finally, apparent ileal digestible lysine based feed formulation was compared to total lysine based feed formulation for broilers (IV). Lysine AID was lower in barley than in triticale and wheat, but did not differ from dehulled oats, oats and maize (II). Methionine AID was the lowest in barley, intermediate in oats, wheat and dehulled oats and highest in maize but maize did not differ significantly from triticale and dehulled oats. In addition, methionine AID in wheat did not differ from dehulled oats and triticale. Furthermore, cysteine AID was highest in wheat, triticale, maize and barleys and lowest in oats but oats did not differ from dehulled oats and maize. Threonine AID was similar among all the grains. Among the protein ingredients, lysine AID was highest in soybean cake, soybean meal and full-fat soybeans, intermediate in rapeseed cake, rapeseed meal and meat and bone meal and lowest in rapeseeds but rapeseeds did not differ from meat and bone meal and rapeseed meal (III). Methionine AID was lowest in meat and bone meal and full-fat rapeseeds, intermediate in full-fat soybeans, rapeseed meal and rapeseed cake and highest in soybean meal and cake, but soybean meal and cake did not differ from rapeseed cake. Cysteine AID was lowest in meat and bone meal and rapeseed meal, intermediate in rapeseed cake and rapeseeds and highest in soybean cake, soybean meal and full-fat soybeans. Threonine AID increased from full-fat rapeseeds and meat and bone meal to rapeseed meal, further to rapeseed cake and onwards to full-fat soybeans, soybean meal and cake. Threonine AID in meat and bone meal did not differ from rapeseed meal, and rapeseed cake did not differ from full-fat soybeans. The AID of cysteine and proline in dried barley containing diets were lower than in air-tightly stored and ensiled barley containing diets (I). The AID of alanine, glutamic acid, isoleucine, methionine, phenylalanine, and proline were lower in air-tightly stored barley compared to that in ensiled barley. The enzyme β-glucanase improved the AID of amino acids in the dried barley containing diet for broilers, but had no effect on the air-tightly stored and ensiled barley containing diets for broilers, or on any diets for cockerels. Amino acid AID was lower in broilers than in cockerels. The predominant basal endogenous amino acids were aspartic acid and glutamic acid and the lowest ones present were methionine and histidine (IV). Lysine and threonine standardised ileal digestibility (SID) was lower in rapeseed meal compared to that in soybean meal and wheat. Methionine SID was similar among soybean meal, rapeseed meal and wheat. Cysteine SID was much lower in soybean meal and rapeseed meal (21.8 and 21.4 %-units lower, respectively) than that in wheat. Differences in amino acid digestibility values of tested ingredients could be explained by variation in chemical composition. Structure of protein fractions and fibre, non-starch polysaccharides and anti-nutritional factors affect digestibility of ingredients. Ingredients with higher fibre content such as cereals and rapeseed products had lower amino acid digestibilities than low fibre ingredients such as soybean meal. The difference between amino acid AID and SID values were the highest in wheat and decreased from rapeseed to soybean meal. The results from growing experiment (III) imply that formulating diets based on a lysine AID was better than that based on total lysine when diets contained protein sources of low amino acid digestibility such as meat and bone meal and rapeseed meal. Variation in the difference between amino acid AID and SID values of different ingredients explains the need to standardise and use standardised amino acid SID values in feed formulation. The amino acid digestibility values measured in current experiments could be added to Finnish feed tables. This would allow formulate more accurately the crude protein-feeding of broilers fed diets composed of different feed ingredients.
Keywords: broiler; cereal; protein ingredient; apparent; standardised; diet formulation